2020
DOI: 10.1099/acmi.0.000102
|View full text |Cite
|
Sign up to set email alerts
|

Shigella sonnei bacteraemia in a cystic fibrosis patient: case report and literature review

Abstract: >Introduction Shigellosis has a gastrointestinal presentation of variable severity in which bacteraemia is uncommon. We describe the first reported case of Shigella sonnei bacteraemia and intestinal coinfection with Clostridioides difficile in a cystic fibrosis patient. The literature on S. sonnei bacteraemia in adult and paediatric populations is also reviewed. Case presentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The study also reported the occurrence of S. dysentrae and S. sonnei which are rare bacterial causing bacteremia. Morduchowicz et al [21], Drews et al [22], and Carretero-Vicario et al [23] reported the occurrence of Shigella sonnei, and Shigella dysentrae as causative agents of bacteremia. The presence of S. dysentrae and S. sonnei in the blood could be the result of comorbidities in the patient that predispose to systemic invasion than the toxin or other virulence factors in specific strains [22].…”
Section: Wondimu Et Almentioning
confidence: 99%
“…The study also reported the occurrence of S. dysentrae and S. sonnei which are rare bacterial causing bacteremia. Morduchowicz et al [21], Drews et al [22], and Carretero-Vicario et al [23] reported the occurrence of Shigella sonnei, and Shigella dysentrae as causative agents of bacteremia. The presence of S. dysentrae and S. sonnei in the blood could be the result of comorbidities in the patient that predispose to systemic invasion than the toxin or other virulence factors in specific strains [22].…”
Section: Wondimu Et Almentioning
confidence: 99%